2021
DOI: 10.1093/ejcts/ezab238
|View full text |Cite
|
Sign up to set email alerts
|

Can prosthesis type influence the recurrence of infective endocarditis after surgery for native valve endocarditis? A propensity weighted comparison

Abstract: OBJECTIVES Our goal was to investigate whether the incidence of valve-related adverse events might be different depending on the valve substitute after valve replacement for left-sided native valve endocarditis. METHODS We assessed the long-term freedom from recurrence, reoperation and survival of 395 patients who had valve replacements for native valve endocarditis (314 mechanical vs 81 biological). Age <18 years, reo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The overall weighted mean age of patients who underwent surgery for infective endocarditis was 55.1 years (95% CI, 52.3-60.2) and was calculated from 11 studies reporting the mean age of all patients [19][20][21][22][23][24][26][27][28][29][30]. Eight studies [21,22,24,27,28,[30][31][32] reported the mean age of patients receiving either a MP or BP. In the mechanical group, the weighted mean age was 49.2 years (CI, 47.1-55.3), and in the biological group, the weighted mean age was 59.8 years (CI, 55.8-63.2).…”
Section: Study Primary Endpoint: Long-term Mortalitymentioning
confidence: 99%
See 4 more Smart Citations
“…The overall weighted mean age of patients who underwent surgery for infective endocarditis was 55.1 years (95% CI, 52.3-60.2) and was calculated from 11 studies reporting the mean age of all patients [19][20][21][22][23][24][26][27][28][29][30]. Eight studies [21,22,24,27,28,[30][31][32] reported the mean age of patients receiving either a MP or BP. In the mechanical group, the weighted mean age was 49.2 years (CI, 47.1-55.3), and in the biological group, the weighted mean age was 59.8 years (CI, 55.8-63.2).…”
Section: Study Primary Endpoint: Long-term Mortalitymentioning
confidence: 99%
“…In the mechanical group, the weighted mean age was 49.2 years (CI, 47.1-55.3), and in the biological group, the weighted mean age was 59.8 years (CI, 55.8-63.2). Twelve studies [20,21,[23][24][25][26][27][28][29][30][31][32] reporting on 8285 patients with infective endocarditis, including 4517 patients with MP and 3768 with BP, analyzed the overall long-term comparison between MP and BP, with a median follow-up ranging from 1 to 15.3 years (20,27). The longest follow-up was 20 years [20].…”
Section: Study Primary Endpoint: Long-term Mortalitymentioning
confidence: 99%
See 3 more Smart Citations